2017
DOI: 10.1590/abd1806-4841.20174898
|View full text |Cite
|
Sign up to set email alerts
|

Schamberg's disease: case report with therapeutic success by using colchicine

Abstract: Pigmented purpuric dermatoses (PPD) include a spectrum of diseases with different clinical aspects, but with similar histopathological features. Specific clinical findings allow the division of PPD in variants. Schamberg's disease is the most common. Treatment is sometimes ineffective and recurrences are common. There are reports of patients who responded well to the use of colchicine. We report the case of a 32-year-old woman, previously healthy, with a history of onset of asymptomatic lesions in legs. She pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Schamberg's disease, also known as progressive pigmented purpuric dermatosis, is the most common form of PPD and typically shows a caudal-cranial progression of the red-brown pigmentation. Lichen aureus is an uncommon type of PPD and is clinically characterized by solitary or multiple rust macules, papules or plaques [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Schamberg's disease, also known as progressive pigmented purpuric dermatosis, is the most common form of PPD and typically shows a caudal-cranial progression of the red-brown pigmentation. Lichen aureus is an uncommon type of PPD and is clinically characterized by solitary or multiple rust macules, papules or plaques [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of SD is unknown. There are studies where are reported that hypertension, venous stasis, exercise, capillary fragility, focal infections, alcohol ingestion and To date, there is no proven effective treatment, but there is general agreement regarding the use of anti-inflammatory drugs to treat skin diseases with immune mediation [4,12,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The lesions initially occur in the lower limbs, but may arise in any area of the body. The disease has a chronic course, with new lesions succeeding the old ones that slowly present bleaching [4,18,24,25]. Pigmented purpuric dermatoses commonly manifests as pigmented spots bilaterally.…”
mentioning
confidence: 99%
“…Additionally, this traditional drug has been reported to be beneficial in numerous other diseases, such as amyloidosis, [23] Wells' Syndrome, [24] Schamberg's disease, [25] junctional epidermolysis bullosa, [26] epidermolysis bullosa acquisita, [27] Hidradenitis suppurativa, [28] lichen planus pigmentosus, [29] aphthous stomatitis (apthosis), Behcets syndrome, [30] condylomata acuminate (as topical solution), palmoplantar pustulosis, psoriasis, scleroderma, urticarial vasculitis as well as sweet syndrome, [3] polychondritis. [31] In a review of Robinson et al the most common indications and their evidence were analyzed (Table 1).…”
Section: Introductionmentioning
confidence: 99%